Interactive Illustrated Book with AR Technology as a Supportive Tool to Help Overcome Anxiety in Early Childhood - Devina Sisilia Sutandy; Aniendya Christianna; Luri Renaningtyas (IJCAS (International Journal of Creative and Arts Studies), 2025)
This study examines the role of interactive illustrated books as supportive educational media for early childhood learners aged 3–6 years, viewed from a visual communication and emotional learning perspective. The research explores how visual storytelling and interactive features, such as pop-up elements, mini activities, and limited augmented reality (AR) integration, can support children’s ability to recognize and manage early experiences of anxiety. A qualitative research approach was employed, involving interviews with child psychologists and early childhood education practitioners, questionnaires distributed to parents, and a literature review. User testing was conducted through individual and group trials to evaluate children’s responses to the designed media. The findings indicate positive responses from children, parents, and teachers in terms of engagement, usability, and emotional expression related to overcoming anxiety in early childhood. The study concludes that interactive illustrated books function not merely as entertainment, but as mediating tools that bridge emotional communication between children and adults. Furthermore, the findings suggest that augmented reality can serve as a complementary feature that enhances engagement without replacing the tactile and relational strengths of physical books in early childhood emotional learning contexts.Buku Ilustrasi Interaktif dengan Teknologi AR sebagai Alat Pendukung untuk Membantu Mengatasi Kecemasan pada Anak Usia Dini AbstrakPenelitian ini mengkaji peran buku bergambar interaktif sebagai media pendidikan pendukung bagi anak usia dini (3–6 tahun), dilihat dari perspektif komunikasi visual dan pembelajaran emosional. Penelitian ini mengeksplorasi bagaimana narasi visual dan fitur interaktif, seperti elemen pop-up, aktivitas mini, dan integrasi augmented reality (AR) yang terbatas, dapat mendukung kemampuan anak dalam mengenali dan mengelola pengalaman awal kecemasan. Pendekatan penelitian kualitatif digunakan, melibatkan wawancara dengan psikolog anak dan praktisi pendidikan anak usia dini, kuesioner yang dibagikan kepada orang tua, serta tinjauan literatur. Uji coba pengguna dilakukan melalui uji coba individu dan kelompok untuk mengevaluasi respons anak-anak terhadap media yang dirancang. Temuan menunjukkan respons positif dari anak-anak, orang tua, dan guru dalam hal keterlibatan, kemudahan penggunaan, ekspresi emosional terkait dengan bagaimana anak usia dini dapat mengatasi kecemasannya. Studi ini menyimpulkan bahwa buku ilustrasi interaktif tidak hanya berfungsi sebagai hiburan, tetapi juga sebagai alat perantara yang menjembatani komunikasi emosional antara anak-anak dan orang dewasa. Selain itu, temuan menunjukkan bahwa realitas tertambah dapat berfungsi sebagai fitur pelengkap yang meningkatkan keterlibatan tanpa menggantikan kekuatan taktil dan relasional buku fisik dalam konteks pembelajaran emosional pada masa kanak-kanak.